Oxytocin modulates neural processing of mitral/tufted cells in the olfactory bulb. (21st February 2021) - Sun, Changcheng; Yin, Zhaoyang; Li, Ben‐Zheng; Du, Han; Tang, Keke; Liu, Penglai; Hang Pun, Sio; Lei, Tim C.; Li, Anan
Abstract: Aim: Oxytocin plays an important role in social recognition in rodents, which is mediated predominantly by the olfactory system. Although oxytocin modulates neural activity in the olfactory bulb, the underlying mechanism is largely unknown. Here, we studied how direct infusion of oxytocin into the olfactory bulb affect social interactions in mice and modulate the neural activity of mitral/tufted cells in the olfactory bulb. Methods: A three‐chamber social interaction test was used in the behavioural test. For in vivo studies, single unit recordings, local field potential recordings and fibre photometry recordings were used to record the neural activity of olfactory bulb. For in vitro studies, we performed patch clamp recordings in the slice of the olfactory bulb. Results: Behaviourally, direct oxytocin infusion in olfactory bulb increased performance in a social interaction task. Moreover, odour‐evoked responses of mitral/tufted cells and neural discrimination of odours were both enhanced by oxytocin, whereas the spontaneous firing rate of mitral/tufted cells was reduced. At the neural network level, oxytocin decreased the amplitude of odour‐evoked high gamma responses. At the cell population level, oxytocin decreased odour‐evoked calcium responses (reflecting neural activity) specifically in granule cells. Moreover, in vitro slice recordings revealed that the inhibitory effect of oxytocin on mitral cell activity is mediated mainly by modulation of ATP‐sensitive potassium channels and involves the oxytocin receptor–Gq–PLC–IP3 signalling pathway. Conclusion: Oxytocin modulates social interaction, likely by increasing the signal‐to‐noise ratio of odour responses in mitral cells which is partly through ATP‐sensitive potassium channel.